An Analysis Of Value Added Tax And Income Tax Article 21 On Tax Payable At PT. Bintang Utama - Suharjono; Jihan Oktaviani; Andi Muhammad Sadli (Sekolah Tinggi Ilmu Ekonomi Mulia Pratama, 2021)
This study aims to determine whether the error in inputting value added tax and calculating income tax article 21 has an effect on the tax payable at PT. Bintang Utama Sentosa. This research was conducted at PT. Bintang Utama Sentosa having its address at JL. WR Supratman No.06, Cimuning with the time of the study being conducted from June to August 2021. The source of the data used in this study was taken from financial reports regarding tax payments within the company. Technical data collection through observation, interviews, and documentation. Data analysis methods used are quantitative and descriptive methods. This research result are the value added tax payable can affect the tax payable, namely the value added tax payable in 2019 amounting to 2,028,660.00, while the calculation of the income tax article 21 can also affect the tax payable, namely in 2019 the company must paid 4,602,266.72.